Credit Deployment by Regional Rural Banks in North East India: A Comparative Study of Assam Gramin Vikash Bank and Tripura GraminBank - Kashyap , Pinkumoni; Adhikari , Kingshuk; Dey, Nikhil Bhusan (Gyan Management Journal, 2016)
The present paper makes a modest attempt to study the growth of credit deployment performance of Assam Gram in Vikash Bank (AGVB) vis-a-vis Tripura Gram in Bank {TGB) from the year 2006 to 2013. In order to compare the growth of credit, parameters like total advance, advance per branch and employee, interest earned on advance, priority, non-priority sector advances and recovery have been used. Analysis of data has been made by employing Compound Annual Growth Rate, Coefficient of Variation and t-test. The growth of total advance of AGVB is found to be higher as compared to the growth of total advance of all TGB. It is clear from the analysis that AGVB is giving more weightage to the priority sector than the non-priority sector by providing proportionately more advances to fulfill the motto of development of socio-economic condition of rural people of the state.
Keywords: Credit; Growth; Recovery; Trend